2012
DOI: 10.1016/j.chb.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A social network as information: The effect of system generated reports of connectedness on credibility on Twitter

Abstract: a b s t r a c tSocial media have gained increased usage rapidly for a variety of reasons. News and information is one such reason. The current study examines how system-generated cues available in social media impact perceptions of a source's credibility. Participants were asked to view one of six mock Twitter.com pages that varied both the number of followers and the ratio between followers and follows on the page and report their perceived source credibility. Data indicate that curvilinear effects for number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(175 citation statements)
references
References 28 publications
3
164
0
8
Order By: Relevance
“…One notable dearth is in understanding how inherent system cues of Facebook and Twitter-the two most commonly used social media platforms-influence users. This is of particular importance because seminal research conducted by Westerman et al (2012) found notable differences in perceptions of credibility based on the number of friends a mock Twitter user had. Thus, not only is it important to understand which social media channel (e.g., Facebook, Twitter) is preferred in times of crisis, but consideration of the effects of system-generated cues is also necessary.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…One notable dearth is in understanding how inherent system cues of Facebook and Twitter-the two most commonly used social media platforms-influence users. This is of particular importance because seminal research conducted by Westerman et al (2012) found notable differences in perceptions of credibility based on the number of friends a mock Twitter user had. Thus, not only is it important to understand which social media channel (e.g., Facebook, Twitter) is preferred in times of crisis, but consideration of the effects of system-generated cues is also necessary.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…People tend to prefer articles, which appear to be appreciated and selected by a large number of other users (Sundar & Nass, 2001) and also, they want to be informed about social reality from other members of the social groups they belong to (Neuman, Just, & Crigler, 1992). This may also have an impact on the audience involved, in the number of the involved users, in the corresponding news-related social media (i.e., the number of followers on Twitter), an issue that is further associated with perceived credibility (Westerman et al, 2012). Users' observations of such published content function as feedback through recommendation-ratings procedures (Lee, 2012) adding at the same time value to the content, thus influencing ourselves and others (Stavrositu & Kim, 2014).…”
Section: Third-person Effect and The Webmentioning
confidence: 99%
“…Diverse popularity metrics can affect user's perceptions of content credibility (Westerman et al, 2012), as well as selective exposure to online news (Knobloch-Westerwick et al, 2005).…”
Section: Social Network and Information Sharing Motivesmentioning
confidence: 99%
“…Sociologists may focus on the bounded nature of community members and seek to ensure that only trusted contributors participate [30]. Natural language researchers may study the inherent sentiment or linguistic patterns in the millions of posts, looking for indicators of credible content.…”
Section: Framework For Credible Communitiesmentioning
confidence: 99%
“…Network analysis to reveal past histories of troubling relationships with known malefactors could be a powerful approach [9,10,11,30]. In some cases, such as with Twitter, follower and following relationships are accessible so deeper understanding of social relationship is possible, but clever users have developed strategies to appear trustworthy or cover troubling histories.…”
Section: Framework For Credible Communitiesmentioning
confidence: 99%